Parent-child cohesion, self-esteem, and academic achievement: The longitudinal relations among elementary school students. (June 2021) - Wang, Yanhui; Huebner, E. Scott; Tian, Lili
Abstract: This study addressed the longitudinal reciprocal relations among parent-child cohesion, self-esteem, and academic achievement in elementary school students. A total of 659 students from Grades 4–5 in China ( M age = 10.09 years, 46.3% female) was investigated on five occasions across 12 months. The results indicated that: (a) For the direct reciprocal relations, mother-child cohesion and academic achievement reciprocally enhanced each other; self-esteem and academic achievement transactionally facilitated each other; father-child cohesion and self-esteem reciprocally enhanced each other; self-esteem facilitated mother-child cohesion, but not vice versa. (b) For the indirect relations, father-child cohesion and students' academic achievement facilitated each other indirectly via self-esteem; students' academic achievement influenced mother-child cohesion indirectly via self-esteem, but not vice versa. These results delineated the dynamic system among these study variables, and also revealed that father-child cohesion and mother-child cohesion showed both similarities and differences. Implications for educational practices were discussed. Highlights: Parent-child cohesion, self-esteem (SE), and academic achievement (AA) were studied. Mother-child cohesion (MCC) and AA, SE and AA were reciprocally related. Reciprocal relations also existed between father-child cohesion (FCC) and SE. SE improved MCC directly, but not vice versa. The indirect paths of AA.→SE→FCC, FCC→SE→AA, and AA→SE→MCC were supported.